Density of herbaceous plants and distribution of western gorillas in different habitat types in south‐east Cameroon. (31st August 2012) - Willie, Jacob; Petre, Charles‐Albert; Tagg, Nikki; Lens, Luc
Abstract The study of forest herb availability improves knowledge of ecology and conservation of gorillas that depend on such herbs. Density patterns of herbs and location of western gorilla nest sites were studied in different habitat types at a site in south‐east Cameroon to assess their relationship. Herb stems of the families Marantaceae and Zingiberaceae were identified and counted in 10, 713 1‐m2 plots distributed within six habitat types. Stem density correlated with light availability and ranged from 2.38 stems m−² in near primary forest to 4.66 stems m−² in light gaps. Gorillas showed marked preferences for habitats with high herb densities such as light gaps, swamps and young secondary forest. However, no clear relationship exists between terrestrial herbaceous vegetation and gorilla densities across Central Africa. It is suggested that differences in ecological factors and land use history within and between sites may explain differences in herb density and diversity which partly account for variations in the historical and present population distribution and density of western gorillas. Formerly logged and swamp forests, which are characterized by an abundance of herbs, may prove to be of great value in the conservation of western gorillas given appropriate forest management practices, adequate protection from poaching and limited human encroachment.